Rancang Bangun Game Edukasi Bencana Alam Menggunakan Metode MDLC - Nisya, Intan Sofiatun; Wulansari, Ossy Dwi Endah; Wartariyus, Wartariyus (Jurnal Ilmu Siber dan Teknologi Digital, 2023)
Purpose: Educational games about natural disasters in Indonesia, as a provision of learning tools to foster children's interest in learning knowledge and emergency response efforts to natural disasters, through digital games that make children happy and easy to understand material. Research Methodology: In making this Natural Disaster Educational Game, the Multimedia Development Life Cycle (MDLC) system development method is implemented which consists of six stages, namely concept, design, material collecting, assembly, testing. and distribution (distribution). This research involved elementary school students and teachers as well as employees of the national disaster management agency in the city of Bandar Lampung. Result: A multimedia-based "Natural Disaster Educational Game" (Case Study for Elementary School Students) has been successfully created as a natural disaster education medium which is a complement to material related to natural disasters in Indonesia, a digital game that makes children happy and easy to understand the material. Limitation: Educational games about natural disasters in Indonesia, including floods, landslides, earthquakes, tsunamis, volcanic eruptions, tornadoes including an introduction to natural disasters in Indonesia, the pre-disaster phase, the emergency response phase. Contribution: Educational games are interactive learning media in terms of knowledge fun, useful for improving language and thinking skills, increasing concentration and solving problems.